Synergistic effect of 2D Ti2C and g-C3N4 for efficient photocatalytic hydrogen production. Issue 32 (26th July 2017) - Shao, Mengmeng; Shao, Yangfan; Chai, Jianwei; Qu, Yuanju; Yang, Mingyang; Wang, Zeli; Yang, Ming; Ip, Weng Fai; Kwok, Chi Tat; Shi, Xingqiang; Lu, Zhouguang; Wang, Shijie; et al.
Abstract : The novel photocatalyst Ti2 C/g-C3 N4 exhibits substantially enhanced water splitting activities due to its improved light absorbance, efficient separation of photoinduced carriers and large surface area. Abstract : Photocatalytic water splitting is an environmentally friendly technique for hydrogen production. In this work, we report a novel photocatalyst consisting of two-dimensional (2D) titanium carbide (Ti2 C) and graphitic carbon nitride (g-C3 N4 ). We observe substantially enhanced water splitting activities due to the efficient synergistic interaction between Ti2 C and g-C3 N4 . Optimal properties are achieved in the g-C3 N4 with a loading of 0.4 wt% Ti2 C with a hydrogen production rate of 47.5 μmol h −1, which is 14.4 times as much as that in the case using pure g-C3 N4, and it even outperforms Pt-loaded g-C3 N4 . We further show that the Ti2 C/g-C3 N4 has high stability and good reproducibility. We expect that the Ti2 C/g-C3 N4 can be a photocatalyst for large scale applications because both Ti2 C and g-C3 N4 are low-cost, abundant, and nontoxic.